Fall episodes in elderly patients with asthma and COPD – A pilot study. (3rd June 2019) - Bozek, Andrzej; Jarzab, Jerzy; Hadas, Ewa; Jakalski, Marek; Canonica, Giorgio Walter
Abstract: Objective : Evidence of an increased risk of falls in patients with chronic obstructive pulmonary disease (COPD) exists; however, this has not been studied in elderly asthmatic patients. The aim of the study was to determine the incidence of falls in elderly patients who were diagnosed with bronchial asthma compared to subjects with COPD. Methods : A 12-month prospective observational study in elderly outpatients with diagnosis of either asthma or COPD was conducted. All of the participants were monitored on the following parameters: falls, comorbidities, drug therapy, and The Berg Balance Scale. The rate of falls was shown as an incidence ratio. Cluster analysis for subgroups with similar features was performed on all patients included in the study. Two clusters of frequent fallers were determined. Results : The fall incidence rate in falls per person per year was 1.41 (95% CI: 0.86–1.96) in asthmatic patients and 1.49 (95% CI: 1.05–2.11) in the COPD group. Frequent fallers were more prevalent in the COPD group, with 32% in this group compared to 28% in the groups of patients with asthma. In cluster analysis, frequent fallers were grouped into two models characterized by polytherapy, depression symptoms, hospitalizations, coronary disease, dementia, and diagnosis of COPD or asthma. Conclusion : Elderly asthmatic patients presented a high rate of falls, which is comparable to that of patients with COPD.